2012
DOI: 10.1177/1461444812451571
|View full text |Cite
|
Sign up to set email alerts
|

Elderly people and morality in virtual worlds: A cross-cultural analysis of elderly people’s morality in interactive media

Abstract: This study examines elderly people's innate moral foundations in influencing decisions, and their subsequent enjoyment in an interactive media environment. The Moral Foundation Questionnaire was used to distinguish between the moral intuitions of elderly US and German respondents, who were believed to have divergent yet stable moral codes that would be salient in a novel virtual world. In an experimental design, participants (N=116) were confronted with a computer simulation in which they could decide to viola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Early research in this line of study examined the model's application of MFT using simple narratives to test specific bivariate relationships (Tamborini, Eden, Bowman, Grizzard, & Lachlan, ) as well as more complex predictions of entertainment's appeal (Eden & Tamborini, 2010; Tamborini, Eden, et al, ). Later research examined the model's broader application of MFT in a more natural setting to character judgments (Eden, Oliver, Tamborini, Woolley, & Limperos, ), decision‐making in video games (Weaver & Lewis, ), and human behavior in virtual worlds (Dogruel, Joeckel, & Bowman, ). These results are important for indicating that MFT's intuitive moral domains may guide responses to popular media experience, and they provide evidence of how the MIME can help us understand the mechanisms through which audiences evaluate entertainment content.…”
Section: The Model Of Intuitive Morality and Exemplarsmentioning
confidence: 99%
“…Early research in this line of study examined the model's application of MFT using simple narratives to test specific bivariate relationships (Tamborini, Eden, Bowman, Grizzard, & Lachlan, ) as well as more complex predictions of entertainment's appeal (Eden & Tamborini, 2010; Tamborini, Eden, et al, ). Later research examined the model's broader application of MFT in a more natural setting to character judgments (Eden, Oliver, Tamborini, Woolley, & Limperos, ), decision‐making in video games (Weaver & Lewis, ), and human behavior in virtual worlds (Dogruel, Joeckel, & Bowman, ). These results are important for indicating that MFT's intuitive moral domains may guide responses to popular media experience, and they provide evidence of how the MIME can help us understand the mechanisms through which audiences evaluate entertainment content.…”
Section: The Model Of Intuitive Morality and Exemplarsmentioning
confidence: 99%
“…Finally, a number of studies have utilized cross-cultural quantitative measures of belief, morality, and values to investigate other topics. For example, the constructs of morality has been used to compare Muslim and Christian ethics in Britain and France (Croucher 2011), elderly German and U.S. citizens moral interactions in virtual spaces (Dogruel et al 2013), and Kantian duty violations between individuals in the United States and Korea (An and Trafimow 2014). Likewise beliefs have been cross-investigated with other measures such as social cynicism belief and social dominance orientation between the United States, Russia, and Portugal (Alexandra et al 2017); social beliefs and consumer behavior (Berkín 2018); and Turkish and Kyrgyz students' beliefs and notions of justice (Karadag and Akgün 2016).…”
Section: Integrative Approachesmentioning
confidence: 99%
“…(17) Core human values such as honesty, sincerity, morality, humanity, non-violence are getting affected because of poverty, unsocialibility, caste system, gender inequality, ill treatment to child women and elders. (17,19) Indians generally say that in their society children have long felt a deep social-moral obligation in their culture to care for elderly parents. According to these mores, adult children-especially sons and daughters-inlaw-live with and care for their elderly parents out of love, a deep respect for them, and a deep sense of moral.…”
mentioning
confidence: 99%
“…Even spiritually, duty to attempt to repay the inerasable debts they owe their parents for all the effort, expense, and affection their parents expended to produce and raise them. (19) Being belonging to a family with social support can enhance the elders' moral values such as acceptance, dependability, cooperation, life satisfaction and happiness. (20) It was reported that happiness as a moral value in old age can be acquired through high social support,which in turn reflected on the elders physical, psychological health and their quality of life.…”
mentioning
confidence: 99%